2008
DOI: 10.1016/j.ica.2007.07.029
|View full text |Cite
|
Sign up to set email alerts
|

Assignment of pre-edge features in the Ru K-edge X-ray absorption spectra of organometallic ruthenium complexes

Abstract: The nature of the lowest energy bound-state transition in the Ru K-edge X-ray Absorption Spectra for a series of Grubbs-type ruthenium complexes was investigated. The pre-edge feature was unambiguously assigned as resulting from formally electric dipole forbidden Ru 4d←1s transitions. The intensities of these transitions are extremely sensitive to the ligand environment and the symmetry of the metal centre. In centrosymmetric complexes the pre-edge is very weak since it is limited by the weak electric quadrupo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
46
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 45 publications
(55 citation statements)
references
References 34 publications
4
46
0
Order By: Relevance
“…The absence of any distinct pre-edge feature implies a centrosymmetric coordination of the here investigated Ru compounds. 52 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The absence of any distinct pre-edge feature implies a centrosymmetric coordination of the here investigated Ru compounds. 52 …”
Section: Resultsmentioning
confidence: 99%
“…For 1 it was found that the indazole ligands are weaker donors toward Ru than imidazole ones, which is congruent with the proposed activation by reduction mechanism stated for 1 and its easier reduction to Ru(II) compared to the imidazole analogue trans -[tetrachlorobis(1 H -imidazole)ruthenate(III)] (KP418). 30,51 Getty et al 52 assigned Ru K-edge pre-edge peaks to the centrosymmetric structure of Ru carbene complexes for olefin metathesis. With increasing symmetry of the complexes the pre-edge peaks got weakened, which was ascribed to a lowered Ru 4d–5p orbital mixing.…”
Section: Introductionmentioning
confidence: 99%
“…octahedral) around the metal; this is a common method of quantifying transitions from octahedral (no pre‐edge) to tetrahedral (strong pre‐edge) environments in metals. In the case of Ru, a weak pre‐edge shoulder is expected at 22 118 eV for non‐inversion‐symmetric species . The lack of this feature in oxidized Ru(acac) 3 (Figure ) indicates octahedral symmetry is maintained.…”
Section: Resultsmentioning
confidence: 98%
“…In the case of Ru, aw eak pre-edges houlder is expected at 22 118eVf or non-inversion-symmetrics pecies. [42] The lack of this feature in oxidized Ru(acac) 3 (Figure 5) indicates octahedral symmetry is maintained. Insights derived from resultsp resented in this paper are being used to functionalize the acetylacetone to mitigate side reactions.…”
Section: Chargedistribution During Reduction and Oxidationmentioning
confidence: 99%
“…Moreover, Ru/h-YbFeO 3 (ST-250) and Ru/h-YbFeO 3 (ST-230) exhibited a pre-edge peak at around 22110 eV. The existence of the pre-edge peak implies that the Ru species is distorted from the octahedral symmetry, 15), 16) suggesting that the distorted Ru species were formed on h-YbFeO 3 (ST-250) and YbFeO 3 (ST-230).…”
Section: Combustion Activities Of Noble Metal Catalystsmentioning
confidence: 99%